Contrasts and positions in information structure - Kučerová, Ivona; Neeleman, Ad (Cambridge University Press, 2012)
Sažetak: "Information structure, or the way the information in a sentence is 'divided' into categories such as topic, focus, comment, background, and old versus new information, is one of the most widely debated topics in linguistics. This volume incorporates exciting new work on the relationship between syntax and information structure. The contributors are united in rejecting accounts that assume designated syntactic positions associated with specific information-structural interpretations, and aim instead to derive information-structural conditions on word order and other phenomena from the way syntax and syntax-external systems interact. Beyond this shared aim, the authors of the various chapters advocate a number of approaches, based on different types of data (syntactic, semantic, phonological/phonetic) from a range of languages. The book is aimed at specialists in syntax and/or information structure, as well as students and linguists in related fields keen to familiarise themselves with current issues in this fascinating area of research".